2015
DOI: 10.1016/j.anbehav.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural strategies associated with using an ephemeral roosting resource in Spix's disc-winged bat

Abstract: The limited availability of refuges may represent an important factor promoting the evolution of sociality, particularly in bats. Spix's disc-winged bats (Thyroptera tricolor) show highly specialized morphological adaptations that enable individuals to roost inside furled musoid leaves. This roosting ecology presents major challenges, as leaves rapidly unfurl, forcing bats to locate new roosts on a daily basis. Despite the reliance of T. tricolor on such ephemeral roosting resources, bats form stable group ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
16
2
Order By: Relevance
“…Contact calls represent a particular type of social call directed primarily towards roost mates; to facilitate recognition, social calls encode individual or group ‘signatures’. For example, in pallid bats ( Antrozous pallidus ), vampire bats, and Spix's disc‐winged bats ( Thyroptera tricolor ), social calls have individual signatures (Fenton et al, ; Arnold & Wilkinson, ; Carter et al, ; Gillam & Chaverri, ) which allow bats to discriminate, and preferentially join, group members within roosts but also during flight (Chaverri et al, ; Montero & Gillam, ). Contact calls may be additionally used to retrieve group mates before foraging (Boughman & Wilkinson, ).…”
Section: Why Do Bats Communicate?mentioning
confidence: 99%
See 1 more Smart Citation
“…Contact calls represent a particular type of social call directed primarily towards roost mates; to facilitate recognition, social calls encode individual or group ‘signatures’. For example, in pallid bats ( Antrozous pallidus ), vampire bats, and Spix's disc‐winged bats ( Thyroptera tricolor ), social calls have individual signatures (Fenton et al, ; Arnold & Wilkinson, ; Carter et al, ; Gillam & Chaverri, ) which allow bats to discriminate, and preferentially join, group members within roosts but also during flight (Chaverri et al, ; Montero & Gillam, ). Contact calls may be additionally used to retrieve group mates before foraging (Boughman & Wilkinson, ).…”
Section: Why Do Bats Communicate?mentioning
confidence: 99%
“…Both signals have signatures that allow bats to discriminate, and preferentially join, members of their own group (Gillam & Chaverri, 2012;Chaverri et al, 2013). This call-and-response system has only been recorded during the day and in this single context (Montero & Gillam, 2015), suggesting that the main function of this exchange of acoustic signals is the active recruitment of roost companions.…”
Section: (B) Roostsmentioning
confidence: 99%
“…Though, it is interesting to call the attention that T. devivoi from Jalapão was collected in a "vereda" rich in Heliconia (Gregorin et al 2006) while we found the species in dead leaves. As with most of the available information about the family, little is known about the acoustic biology of Thyropteridae, and that which exists mainly refers to two species (T. discifera and T. tricolor), with some studies focused on social calls (Chaverri et al 2010, 2013, 2015, Montero & Gillam 2015, while others concentrated on echolocation calls (Fenton et al 1999, Tschapka et al 2000, Barataud et al 2013, Rivera-Parra and Burneo 2013. Echolocation calls of T. devivoi recorded by us are of low intensity, which make them difficult to detect (Fenton et al 1999, Dechmann et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…This allows the bats to obtain high-quality detailed information on their surroundings (Schnitzler and Kalko 2001). We recorded a social call similar to that described by Montero and Gillam (2015) for T. tricolor, who qualified it as SQCF (short quasi-constant frequency). We do not know the purpose of this call for T. devivoi, but it is present during certain times of the night between periods of echolocation and, therefore, may possibly be emitted in flight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation